Father's Support and Mother's Behavior in Stunting Prevention Efforts - Dhani Syahputra Bukit; Alam Bakti Keloko; Taufik Ashar (Journal of Health Science and Prevention, 2021)
Stunting is the nutritional quality of infants under five years of age according to age compared to the usual benchmarks according to the World Health Organization's Multicentre Growth Reference Study in 2006. The incidence of stunting in infants under five years of age is a problem that exists in Indonesia and is a major nutritional problem. Data from the results of monitoring the quality of nutrition in the previous three years period has the highest prevalence compared to other nutritional problems such as malnutrition, thinness, and obesity. The purpose of this study was to analyze the correlation of the father's support and mother's behavior in Stunting Prevention Efforts in Tuntung 2 Village, Pancur Batu District, Deli Serdang Regency using a cross-sectional design. This study was done on 135 mothers who have infants aged 6-59 months as respondents. The variables in this study were father's support related to stunting prevention and the dependent variable in this study is the behavior of the mother in preventing stunting. The results showed that there was a significant correlation of the father's support and mothers’ behavior in preventing stunting (p <0.038). To increase efforts of prevent stunting, it is hoped that fathers who have not supported their wives should be more concerned about their toddler's growth and health.